Carbon dot reduced bimetallic nanoparticles: size and surface plasmon resonance tunability for enhanced catalytic applications1. Issue 31 (21st August 2015) - Essner, Jeremy B.; Laber, Charles H.; Baker, Gary A.
<x xml:space="preserve">Abstract</x> Carbon dots derived from citric acid pyrolysis were competent reductants and stabilizing agents in the eco-friendly preparation of Ag, Au, and bimetallic AuAg nanoparticles which presented plasmonic, size, and catalytic tunability.